The Role of Public Policy and Digital Connectivity in Driving Gdp Growth: A Cross-Country Study of Emerging Economies - Sakti, Rachmad Kresna; Mubarak, Muhammad Faraz; Setyanti, Axellina Muara; Prestianawati, Silvi Asna (Economics, Business, Accounting & Society Review, 2026)
This study examines how digital connectivity and public policy influence economic growth in developing countries, utilizing data from 21 nations spanning the years 2018 to 2023. The study focuses on internet adoption rates, internet speed, government policies, and GDP growth rates, employing a composite index and Panel-Corrected Standard Errors (PCSE) regression method. The findings indicate that higher internet penetration, faster internet speed, and enhanced internet security are positively associated with per capita GDP growth, highlighting the importance of digital connectivity in fostering economic development. In contrast, reliance on basic cellular connections shows a negative impact on per capita GDP, potentially due to lower productivity associated with basic mobile usage. The study also emphasizes the crucial role of public policy performance, which demonstrates a strong positive correlation with economic growth, suggesting that effective governance and well-implemented policies are essential for maximizing the benefits of digital infrastructure in driving economic progress. The study's integration of both digital connectivity variables and public policy provides new insights into the synergies between technology and governance, offering a comprehensive view of how these factors together influence economic outcomes. This approach adds valuable contributions to development economics, particularly in understanding the roles of modern digital infrastructure and policy frameworks in supporting sustainable growth in developing countries.